The curious case of C-88: impacts of a potato variety on farmers in Yunnan, China - Stephanie Myrick; Willy Pradel; Canhui Li; Victor Suarez; Guy Hareau; Catherine Larochelle; George W. Norton; Jeffrey Alwang (CABI Agriculture and Bioscience)
Abstract Background Limited analysis has been conducted of the role of agricultural research in promoting Chinese agricultural growth in less-favored areas. This paper analyzes how a particular potato variety generates benefits to producers and discusses how these benefits may have contributed to poverty reduction in Yunnan province. Cooperation 88 (C88) is a high-yielding, late blight-resistant variety that was developed through a partnership between the International Potato Center and Yunnan Normal University in Kunming, China. Methods Qualitative and quantitative methods are used to analyze determinants of adoption of C88, and to estimate impacts of adoption on producer well-being. A unique farm-household database is used to document the determinants of C88 adoption and disadoption. The quantitative assessment is supplemented with a qualitative analysis of the potato value chain to understand how seed availability and concern for processing attributes contributed to and eventually constrained diffusion. Market-level information was used in an economic surplus model to quantify the substantial economic impact of C88 over 20 years since its release. Results C88 spread rapidly in Yunnan following its release and was widely adopted by commercially oriented farmers. Disadoption began after 2010 with limited seed availability driving the shift toward newer varieties. Farmers, however, appreciate the ease of marketing, the 15% higher yields, and late-blight resistance associated with C88 suggesting that seed constraints are countervailing the economic benefits of the variety. Total impact on Yunnan potato farmers of the variety was estimated to be around $2.5 billion for the 1996–2015 period. Conclusions On per-person terms among C88 growing farm households, the economic advantage of the variety is likely to have contributed to poverty reduction. The aggregate impact of C88 diffusion occurred during a period of rapid poverty reduction in Yunnan and yield and disease-resistance benefits of C88 likely contributed to this reduction.